Adenovirus-mediated gene delivery restores fertility in congenitally infertile female mice - Mito KANATSU-SHINOHARA; Jiyoung LEE; Takehiro MIYAZAKI; Hiroko MORIMOTO; Takashi SHINOHARA (The Society for Reproduction and Development, 2022)
Oogenesis depends on close interactions between oocytes and granulosa cells. Abnormal signaling between these cell types can result in infertility. However, attempts to manipulate oocyte-granulosa cell interactions have had limited success, likely due to the blood-follicle barrier (BFB), which prevents the penetration of exogenous materials into ovarian follicles. Here, we used adenoviruses (AVs) to manipulate the oocyte-granulosa cell interactions. AVs penetrated the BFB and transduced granulosa cells through ovarian microinjection. Although AVs caused transient inflammation, they did not impair fertility in wild-type mice. Introduction of Kitl-expressing AVs into congenitally infertile KitlSl-t/KitlSl-t mutant mouse ovaries, which contained only primordial follicles because of a lack of Kitl expression, restored fertility through natural mating. The offspring showed no evidence of AV integration and exhibited normal genomic imprinting patterns for imprinted genes. These results demonstrate the usefulness of AVs for manipulating oogenesis and suggest the possibility of gene therapies for human female infertility.